Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Don Forbes, Nancy Smith, Leslie Helon, Marvin T. Helon, ??, Nancy C. Cisneros, and David Cisneros